A biomimicing approach to the mixed ligand complexes of bivalent transition metal - Prasad, Bipin Bihari; Sah, Ramjee (International Journal of Applied Sciences and Biotechnology, 2013)
Metal complexes of the type ML1L2[M=Cu(II), Ni(II), and Co(II), L1=?,?'-dipyridyl(dipy.), L2=2-hydroxybenzalidine anthranilic acid (HBAA)] have been synthesized by using ?,?'-dipyridyl(dipy.), 2-hdroxybenzalidine anthranilic acid (HBAA) and metal(II) acetate. The resulting mixed ligand metal complexes have been characterized on the basis of elemental analysis, IR-spectra, electronic spectra, magnetic susceptibilities and molar conductance measurements. The antifungal and antibacterial activities of ligands and there metal complexes have been screened against Aspergillus flavus, Aspergillus fumigatus, Aspergillus niger, Escherichia coli and Staphylococcus aureus. DOI: http://dx.doi.org/10.3126/ijasbt.v1i1.7922 Int J Appl Sci Biotechnol, 2013, Vol. 1(1): 16-20